Calidad ambiental de los humedales costeros del departamento de La Libertad, mediante parámetros físicos, químicos y biológicos, 2016 - Bopp Vidal, Geiner Manuel (2019)
ABSTRACT The objective was to determine the environmental quality of the coastal wetlands of the department of La Libertad, through the use of physical-chemical and biological parameters. Sampling was conducted between April 2016 to September 2017. Physical-chemical parameters such as conductivity, water temperature, air, pH and total dissolved solids were used the HACH multiparameter, a MERCK indicator tape for alkalinity. The samples of vascular flora were placed in a botanical press for their herbalization and identification, for the phytoplankton a phytoplankton net of 15 um was used, for the identification of birds the register of direct and indirect observations was used. The vascular flora was represented by 79 species grouped into 18 families, 118 species of phytoplankton were identified, in birds 148 species were identified, in 18 orders and 36 families, predominantly the Passeriformes order with 14 families. The physical-chemical parameters, the average air temperature was 24.5 ° C, average surface water temperature 22.3 ° C. Water pH between 6.7-9.0; electrical conductivity 220 to 1065 uS / cm; total dissolved solids between 150 to 1006 ppm and alkalinity between 80 to 240 ppm. It is concluded that the environmental quality of coastal wetlands is in good condition.